Ethnobotanical Study of Postnatal Medicinal Plants in the Ethnic Madurese in Bangkalan Regency, East Java, Indonesia - Siti Muslichah; Rodiyati Azrianingsih; Serafinah Indriyani; Estri Laras Arumingtyas (Indian Journal of Forensic Medicine & Toxicology, 2021)
Postnatal period is a time for women to recover and take on new roles. Plants have an important role in the traditional posnatal care in many cultures around the world especially in rural areas. The use of medicinal plants is common among Madurese women especially to aid postpartum care. This research aimed to record the use of plants for postnatal care among the Madurese in Bangkalan Regency, East Java, Indonesia. Data were collected from local informants consisting of traditional birth attendants, herbal medicine makers, and herbal medicine sellers through open and semi-structured interviews. The data were analyzed quantitatively using the Use Value (UV), Family Use Value (FUV), and Index of Cultural Significance (ICS) parameters. There were 143 species of medicinal plants from 55 families identified as plants used for recovery during the postnatal period. Ginger is a plant that has the highest use value (1.84), followed by turmeric (1.81). There are five plant species which have very high ICS value. Ginger has the highest ICS value (168), followed by turmeric (132). The family with the highest FUV value was Zingiberaceae (0.79). Among the Madurese, medicinal plants are mostly used in multiherbal forms consisting of 2 to 30 plants. There are 13 kinds of concoctions used in postnatal care consisting of 8 multiherbal potions used orally and 5 herbs for external uses. Madurese women believe that the use of these herbs will speed up the postpartum recovery process and reduce postnatal diseases. This valuable knowledge should be continued to be applied by the young generation in order to maintain its existence and to conserve the plants used in this region.